Regulated development of cannibalistic supergiant cells in the ciliate Euplotes gigatrox - Ben T. Larson; Daniele Giannotti; Mahara Mtawali; Samuel J. Lord; Vittorio Boscaro; Patrick J. Keeling (Proceedings of the National Academy of Sciences, 2026)
Virtually all paradigms in developmental biology apply to differentiating cells and tissues within multicellular animals and plants. However, unicellular eukaryotes, which must simultaneously perform all activities necessary for a cell as well as an organism, also form complex and specialized structures, using exclusively subcellular processes. Here, we describe a ciliate ( Euplotes gigatrox sp. nov.) undergoing drastic morphological transformations within a genetically uniform population, the most spectacular being the appearance of “supergiants” that increase in size, change shape, and modify their locomotion and feeding behavior to cannibalize clonal relatives. We explore supergiant formation from the perspective of life cycle, ecological strategy, and gene expression, demonstrating that supergiants are a distinct, regulated, transcriptionally unique stage. Differentiation appears to depend on internal and external conditions, suggesting that regulatory loops have evolved to ensure coupling between environmental and physiological conditions. This system provides a blueprint for approaching both cell differentiation and functional ecology in unicellular organisms, which might open new avenues for the generalization and contextualization of known morphogenetic mechanisms, as well as the discovery of new ones.